Chatbot for E-Commerce Assistance: based on RASA - et. al., M.Mamatha, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Whenever a customer using an Ecommerce sites like Amazon, Flipkart etc, he may face issues which may trouble him. It takes time for the customer support to resolve the customer issues since billions of people are using those platforms and reporting issues regularly. So this makes some congestion on the customer support side, so that they could not react so quickly. One more issues are buying the products by searching from different platforms. This may also takes too much time. So here, adding a bot to the platform which can understand the human language and generate an appropriate response. This bot will be useful for filtering the products from whatever the ecommerce sites it has been incorporated it with(here the own site developed, which runs in local server as other ecommerce api procurement is taking much time than expected) ans also replying to some of the issues before they get to the customer call center.